Extracellular Vesicle-Derived miR-105-5p Promotes Malignant Phenotypes of Esophageal Squamous Cell Carcinoma by Targeting SPARCL1 via FAK/AKT Signaling Pathway - He, Binjun; Zhang, Kang; Han, Xiaoliang; Su, Chao; Zhao, Jiaming; Wang, Guoxia; Wang, Guzong; Zhang, Liuya; Hu, Wenbin (Frontiers in Genetics, 2022)
Objective: Esophageal squamous cell carcinoma (ESCC) is a malignancy with high morbidity and mortality. Recent evidence suggests that vesicles derived from blood can transmit regulating signals and facilitate ESCC development. However, the molecular mechanism of vesicle miRNA secreted by tumor cells affecting ESCC progression has not been explored. Methods: Differentially expressed genes and mRNA-related signaling pathways were screened out in TCGA dataset. Expression of miRNA-105-5p and SPARCL1 was determined by qRT-PCR. Western blot was used for the determination of the protein level. Dual-luciferase reporter assay was utilized to verify the interaction between miRNA-105-5p and SPARCL1. Transmission electron microscope was utilized to further identify extracellular vesicles (EVs), and co-culture assay was performed to validate the intake of EVs. In vitro experiments were conducted to evaluate cell function changes in ESCC. Tumor formation in nude mice experiment was carried out to observe tumor growth in vivo. Results: MiRNA-105-5p was active in ESCC while SPARCL1 was less expressed. MiRNA-105-5p facilitated cell behaviors in ESCC through targeting SPARCL1 and regulating FAK/Akt signaling pathway. Blood-derived external vesicles containing miRNA-105-5p and EVs could be internalized by ESCC cells. Then miRNA-105-5p could be transferred to ESCC cells to foster tumorigenesis as well as cell behaviors. Conclusion: EVs-carried miRNA-105-5p entered ESCC cells and promote tumor-relevant functions by mediating SPARCL1 and FAK/Akt signaling pathway, which indicated that treatment of ESCC via serum EVs might be a novel therapy and that miRNA-105-5p is expected to be a molecular target for ESCC therapy.